Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah Dan Kinerja Keuangan Terhadap Belanja Modal Kabupaten Dan Kota Di Provinsi Jawa Tengah: Penelitian - Elva Intan Mawarni; Rispantyo (Journal of Innovative and Creativity, 2025)
This research aims to examine the influence of General Allocation Funds (DAU), Regional Original Income (PAD) and Financial Performance on Capital Expenditures. The data used in this research is secondary data. The population of this research is all districts and cities in Central Java Province for the 2019-2022 period. The population used was 35 regencies and cities in Central Java Province with a sample of 140. The data analysis technique used was Multiple Linear Regression analysis. The results of this research are that General Allocation Funds (DAU),Regional Original Income (PAD) and Financial Performance have a positive and significant influence on Regency and City Capital Expenditures in Central Java Province in 2019-2022.